2022
DOI: 10.1590/1983-21252022v35n108rc
|View full text |Cite
|
Sign up to set email alerts
|

Germination of Cactus Seeds Under Saline Stress

Abstract: Cactus seeds in seasonal dry tropical forests are subject to several stressors, such as salt stress which limits imbibition and therefore germination. Thus, this study aimed to compare germination performance of Cereus jamacaru subsp. jamacaru and Pilosocereus pachycladus subsp. pernambucoensis seeds under salinity conditions. To this end, NaCl and KCl solutions were used in the following osmotic potentials: 0.0 (control),-0.2,-0.4,-0.6,-0.8,-1.0, and-1.2 MPa. Seeds were placed to germinate at 25 °C and 12-hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…When seeds from the −1.6 MPa treatment were washed and again incubated with water, germination was similar (90% to 99%) to that of the control, suggesting that water stress did not affect viability or germinability of the seeds, as was found for salt stress in Experiment 2. Seeds of C. jamacaru demonstrated a similar level of tolerance to water stress in the study by Silva and de Azerêdo (2022), with germination remaining unaffected at an osmotic potential of −0.6 MPa. However, substantial reductions occurred between −0.6 MPa and −0.8 MPa.…”
Section: Resultssupporting
confidence: 65%
See 3 more Smart Citations
“…When seeds from the −1.6 MPa treatment were washed and again incubated with water, germination was similar (90% to 99%) to that of the control, suggesting that water stress did not affect viability or germinability of the seeds, as was found for salt stress in Experiment 2. Seeds of C. jamacaru demonstrated a similar level of tolerance to water stress in the study by Silva and de Azerêdo (2022), with germination remaining unaffected at an osmotic potential of −0.6 MPa. However, substantial reductions occurred between −0.6 MPa and −0.8 MPa.…”
Section: Resultssupporting
confidence: 65%
“…Conversely, Meiado et al (2010) reported that C. jamacaru exhibited a much higher degree of sensitivity to water stress, with reductions in germination beginning at −0.2 MPa and minimal germination observed at −0.6 MPa and −0.8 MPa. It is worth noting that Silva and de Azerêdo (2022) calculated osmotic potentials from NaCl concentrations using the Van’t Hoff equation (Salisbury and Ross 1991), whereas Meiado et al (2010) established solutions with different osmotic potentials by varying PEG concentrations, mirroring our approach in this research. This suggests that the latter method might be more appropriate for evaluating the germination response to water stress.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…Silva and Azerêdo [64] also observed greater seed germination of two cactus species (Cereus jamacaru and Pilosocereus pachycladus) at a water potential of −0.2 MPa. Germination decreased from −0.2 MPa to −0.8 MPa, reaching zero at −1.0 and −1.2 MPa.…”
Section: Experiments Ii: Germination and Vigor Of Seeds Under Differe...mentioning
confidence: 78%